A Natural Biopolymer Film as a Robust Protective Layer to Effectively Stabilize Lithium‐Metal Anodes. Issue 31 (1st July 2018) - Zhang, Shao‐Jian; Gao, Zhen‐Guang; Wang, Wei‐Wei; Lu, Yan‐Qiu; Deng, Ya‐Ping; You, Jin‐Hai; Li, Jun‐Tao; Zhou, Yao; Huang, Ling; Zhou, Xiao‐Dong; Sun, Shi‐Gang
Abstract: Li metal is considered as an ideal anode for Li‐based batteries. Unfortunately, the growth of Li dendrites during cycling leads to an unstable interface, a low coulombic efficiency, and a limited cycling life. Here, a novel approach is proposed to protect the Li‐metal anode by using a uniform agarose film. This natural biopolymer film exhibits a high ionic conductivity, high elasticity, and chemical stability. These properties enable a fast Li‐ion transfer and feasiblity to accomodate the volume change of Li metal, resulting in a dendrite‐free anode and a stable interface. Morphology characterization shows that Li ions migrate through the agarose film and then deposit underneath it. A full cell with the cathode of LiFPO4 and an anode contaning the agarose film exhibits a capacity retention of 87.1% after 500 cycles, much better than that with Li foil anode (70.9%) and Li‐deposited Cu anode (5%). This study provides a promising strategy to eliminate dendrites and enhance the cycling ability of lithium‐metal batteries through coating a robust artificial film of natural biopolymer on lithium‐metal anode. Abstract : Agarose, a kind of natural biopolymer, is used to construct artificial protective film for the Li‐metal anode. Li ions can diffuse through and deposit under this film, leading to a dendrite‐free surface during repeated Li plating/stripping processes. This film can also reduce the side reaction due to its function as a physical barrier to separate the electrolyte and Li metal.